ANALISIS KOMPARATIF PT BANK SYARIAH INDONESIA TBK. SEBELUM DAN SESUDAH MERGER - Siti Maesaroh; Sri Wahyuni Asnaini (Universitas Insan Pembangunan Indonesia, 2023)
The long-term goal achieved in this study is to see the effect of the merger of BUMN Syariah Banks to become Indonesian Syariah Banks (BSI). Where is the merger will certainly affect the expansion of the market area and can increase product variations because so far each Islamic Bank has unique products that have different characteristics, so that later it will further enrich its products, can increase economies of scale or increase the size of the bank, economics of scope and course this can be realized by financing giant projects. The research method used is a descriptive method with a quantitative approach. The population of this study is PT Bank BRI Syariah Tbk, PT Bank BNI Syariah, and PT Bank Syariah Mandiri. The next step is to process the data using the SPSS 17 software using the Wilcoxon signed rank test so that a research report can be compiled as the activity output. The results of the statistical test analysis there is no significant difference in the values of KPPM, ROA, ROE, NPF, FDR, BOPO, and NOM at Bank BRIS, BNIS, and BSM before and after the Merger. The KPPM, ROA, ROE, and NOM values are negative indicating that the KPPM, ROA, ROE, and NOM values after the merger are higher than before the merger. On the other hand, the NPF, FDR, and BOPO values are positive indicating that the NPF, FDR, and BOPO values after the merger are lower than before the merger.Keywords: Comparative, Financial Ratios, Bank Mergers